2012
DOI: 10.1299/kikaic.78.2781
|View full text |Cite
|
Sign up to set email alerts
|

Study on Landing Response Control of Planetary Exploration Spacecraft Based on Momentum Exchange Principles

Abstract: This paper discusses landing response control methods of planetary exploration spacecrafts on the basis of momentum exchange principles. Concretely, the methods adopt momentum exchange impact dampers (MEIDs) that absorb the controlled object's momentum with extra masses close to the object (damper masses). For example, this paper shows

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 5 publications
(2 reference statements)
0
11
0
Order By: Relevance
“…Hara et al reported a landing method that used a momentum-exchange impact damper (MEID). [4][5][6][7][8][9][10] This method realizes a soft landing by controlling the momentum of a spacecraft by launching damper masses. To increase the momentum exchange efficiency, Kushida et al proposed an active/passive hybrid MEID (HMEID), 7) which uses both active and passive elements for the mass launch.…”
Section: Problems With Conventional Landing Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Hara et al reported a landing method that used a momentum-exchange impact damper (MEID). [4][5][6][7][8][9][10] This method realizes a soft landing by controlling the momentum of a spacecraft by launching damper masses. To increase the momentum exchange efficiency, Kushida et al proposed an active/passive hybrid MEID (HMEID), 7) which uses both active and passive elements for the mass launch.…”
Section: Problems With Conventional Landing Methodsmentioning
confidence: 99%
“…The effectiveness of the G-HMEID was revealed in the previous work. 9) However, this method only performs well with a sufficient amount of mass to launch. Thus, there is a tradeoff between landing performance and weight saving.…”
Section: Problems With Conventional Landing Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Until now, the effectiveness of MEIDs has been demonstrated with simulations and experiments based on a single axis (SA) [5][6][7][8], and the effectiveness of MEIDs in a double-axis scenario has been verified only for AMEID systems [4]. However, actuators increase the overall mass of the system, and may lead to control errors.…”
Section: Introductionmentioning
confidence: 99%